Preparing North American Preservice Teachers for Global Perspectives: An International Teaching Practicum Experience in Africa - Monari Mwebi, Bosire; Brigham, Susan M. (Alberta Journal of Educational Research, 2010)
Given the economic, political, and social conditions in the world today and the increased diversity in Canadian classrooms, schools require teachers who have a strong sense of self-awareness and understanding of global issues. This article is based on empirical research involving preservice teachers from an Atlantic Canadian university. The preservice teachers did six weeks of teaching practicum in Africa. We draw on the theories of Africentricity and transformative learning to inform our analysis. Our findings suggest that preservice teachers who did their practicum in Africa increased their self-awareness, and enhanced their personal efficacy and understanding of cross-cultural, diversity, and globalization issues, which has informed their subsequent teaching practice in public school systems. We conclude with recommendations for teacher education programs.